If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + 2 = 9 Reorder the terms: 2 + t = 9 Solving 2 + t = 9 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + t = 9 + -2 Combine like terms: 2 + -2 = 0 0 + t = 9 + -2 t = 9 + -2 Combine like terms: 9 + -2 = 7 t = 7 Simplifying t = 7
| 7x+4x=60+5x | | 5x-2x=-27 | | 41+(57+15)=150 | | 41+(41+15)=150 | | 41+(x+15)=150 | | -2x-28=-160 | | 4+.3x=5+.1x | | 3t^2+10t-48=0 | | 3x-5=-23 | | 60-11x=80-15x | | 6-3y=9-5y | | 2xy+5x-3y=0 | | =5z^2+16z+3 | | =7y^2-17y+6 | | 3r-12=0 | | 1017=.33x | | 2t+5=8 | | x+3+x+3=10 | | .33x=1017 | | 16x+3y=3 | | .25x=866 | | -6=5(x+3)-6x | | -6=(x+3)+6x | | .33x=.25x | | -6=(x+3)+4x | | c^2-7c-12=0 | | c^2-35-60=0 | | 11x=64+36 | | 2x-3+2x-3=1 | | 5c^2-35c=60 | | 9x=56+2x | | x^4-4*x^3=0 |